The Association between Immunization and Nutritional Status of children aged 12 23 Months in Punggawan Village Banjarsari Districts Surakarta - Rizqa Febriliany Putri; Widardo widardo; Martini martini (Nexus Kedokteran Komunitas, 2016)
Background: Over 6.6 million children under five years old died in 2012. Approximately, 45% of these deaths were caused by malnutrition. Indonesia faced dual problem in childrens nutrition as the proportion of over nutrition was high, approximately 11.9% in 2013. Immunization is an effective method to prevent disease and affect indirectly to childrens nutritional status. However, the increasing immunization coverage in Indonesia did not followed by improved nutritional status among children. The prevalence of under-nutrition kept increasing during 2007-2013. This study aimed to measure the association between immunization and nutritional status among children aged 12 23 months in Punggawan Village, Banjarsari Districts, Surakarta. Methods: An observational analytic study with cross sectional design was conducted. This study was located in Punggawan Village, Banjarsari Districts, Surakarta during June July 2014 time period. Sample of this study was children aged 12 23 months in Punggawan Village, Banjarsari Districts, Surakarta. Sample was taken by non-probability sampling technique using total sampling method. Data were gathered by direct measurement of childrens weight and height. Their nutritional status was defined by several anthropometry indices such as weight for age, height for age, weight for height, and body mass index for age. Childrens immunization status was classified into complete on schedule, complete but not on schedule, and incomplete. Data was analyzed by one-way ANOVA, Kruskal-Wallis test, and T-test. Results: The result of one-way ANOVA test showed p=0.786 means that immunization status was not associated with weight for age index. The result of Kruskal-Wallis test showed that immunization status was not associated with height for age, weight for height, and body mass index for age indices with p value respectively 0.27; 0.214; 0.354. Nutritional status also did not show an association with mothers educational level. On the contrary, T-test results showed an association between mothers job type and weight for age index (p=0.001), weight for height index (p=0.004), height for age index (p=0.002), BMI for age index (p=0.022). Conclusion: There was no association between immunization and nutritional status in 12 23 months children in Punggawan Village, Banjarsari Districts, Surakarta. Keywords: immunization status, nutritional status, anthropometry